SURVEILLANCE OF BACTERIA METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS AND PSEUDOMONAS AERUGINOSA IN PATIENTS ADMITTED TO ORTHOPEDIC DEPARTMENT IN A TERTIARY REFERRAL HOSPITAL - Das, Pulin Bihari; Mishra, Monali Priyadarshini; Rath, Siba Narayan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Methicillin-resistant Staphylococcus aureus (MRSA) strains have emerged independently in diverse geographic zones and MRSA and Pseudomonas aeruginosa cause surgical site infections. Nosocomial surveillance in orthopedic surgery wards of the hospital for 16 months is presented. Methods: A total of 621 wound swabs were cultured on blood and MacConkey agar plates for bacteria and Sabouraud dextrose agar for fungi. Results: From 468 bacterial colonies, 98 MRSA and 74 P. aeruginosa strains and 41 fungal strains were isolated, and fungal strains were 13 strains of Aspergillus niger, and 28 strains of Candida albicans. P. aeruginosa and S. aureus strains were susceptible to antibiotics tobramycin, ciprofloxacin, piperacillin, vancomycin, levofloxacin, and amoxyclav. Similarly, A. niger and C. albicans were susceptible to antifungals, amphotericin B (AMB), liposomal AMB, itraconazole, voriconazole, posaconazole, and caspofungin. Conclusion: Isolated MRSA strains were resistant to presently used common antibiotics, which attribute to the leading causatives of post-operative infection in orthopedic wounds, specifically.